CHARACTERISTICS OF WOUND HEALING AT THIGH DONOR SITES FOLLOWING SPLIT-THICKNESS SKIN GRAFT HARVEST USING CALCIUM ALGINATE HYDROCOLLOID DRESSINGS AT VIET DUC UNIVERSITY (Vietnam Journal of Community Medicine, 2026)
Objectives: To describe wound healing outcomes at thigh donor sites following split-thickness skin graft (STSG) harvest using calcium alginate hydrocolloid dressings at Viet Duc University Hospital.Subjects and Methods: A prospective longitudinal descriptive study was conducted on 47 patients undergoing treatment for donor-site wounds after STSG harvest at the Department of Maxillofacial Surgery, Plastic and Aesthetic Surgery, and the Department of Septic Surgery, Viet Duc University Hospital, from October 2024 to June 2025.Results: The mean age was 38.2 ± 19.3 years, with males accounting for 74.5%. The mean VAS pain score was 4.7 ± 1.2 on postoperative day 1 and decreased to 0.7 ± 0.3 by postoperative day 7 (p < 0.05). The average number of dressing changes was 2.6 ± 1.3, with 74.5% of patients requiring fewer than three changes. The semi-occlusive membrane detached mainly within 7–10 days (76.6%). The wound infection rate was 2.1%. A good care outcome at the donor site was observed in 89.4% of patients. Long-term evaluation showed a higher proportion of good outcomes at T4 compared to T3 (34.0% vs. 27.7%).Conclusions: The use of calcium alginate hydrocolloid dressings for donor-site care appears feasible and safe, with a trend toward reduced pain over time, fewer dressing changes, and a low complication rate. Most patients achieved favorable care outcomes during the follow-up period.
Keywords: Split-thickness skin graft, donor site management, calcium alginate hydrocolloid.